Effects of Ocean Acidification on Coral Endolithic Bacterial Communities in Isopora palifera and Porites lobata - Yang, Sung-Yin; Lu, Chih-Ying; Tang, Sen-Lin; Das, Rocktim Ramen; Sakai, Kazuhiko; Yamashiro, Hideyuki; Yang, Shan-Hua (Frontiers in Marine Science, 2020)
Endolithic microbes in coral reefs may act as a nutrient source for their coral hosts. Increasing atmospheric CO2 concentrations are causing ocean acidification (OA), which may affect marine organisms and ecosystems, especially calcifying organisms such as reef-building corals. However, knowledge of how OA affects marine microbes remains limited, and little research has been done on how coral endolithic communities respond to shifting environmental baselines. In this study, the endolithic communities of two common shallow water coral species, Isopora palifera and Porites lobata, were examined to investigate the microbial community dynamics under OA treatments. The colonies were placed in an environment with a partial pressure of carbon dioxide (pCO2) of 1000 or 400 ppm (control) for two months. Several I. palifera colonies bleached and died at 1000 ppm pCO2, but the P. lobata colonies remained unaffected. Inversely, the endolithic community in P. lobata skeletons showed significant changes after OA treatment, whereas no significant dynamics were observed among the I. palifera endoliths. Our findings suggest that the skeletal structures of different coral species may play a key role in corals host and endoliths under future high-OA scenarios.